TEKNIK PEMERIKSAAN ARTICULATION GENU DENGAN SANGKAAN OSTEOARTHRITIS DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - PANUNTUN, MAHENDRO AJI (JURNAL ILMIAH MAKSITEK, 2023)
The articulatio genu is a complex hinge joint and is formed by the distal part of the femur bone, condyle, epicondyle, proximal part of the tibia bone. Osteoarthritis is a degenerative joint disease that appears to be related to the aging process, obesity or joint trauma. The projection used in the Articulatio Genu examination with suspected Osteoarthritis at the North Sumatra Hospital Medan Installation uses the AP Weigh Bearing projection and lateral projectionThe results of this research are examination of the genu with suspected osteoarthritis using the AP Weigh Bearing projection.